The Role of Short-Chain Fatty Acids and Bile Acids in Intestinal and Liver Function, Inflammation, and Carcinogenesis - Visekruna, Alexander; Luu, Maik (Frontiers in Cell and Developmental Biology, 2021)
During the past decade, researchers have investigated the role of microbiota in health and disease. Recent findings support the hypothesis that commensal bacteria and in particular microbiota-derived metabolites have an impact on development of inflammation and carcinogenesis. Major classes of microbial-derived molecules such as short-chain fatty acids (SCFA) and secondary bile acids (BAs) were shown to have immunomodulatory potential in various autoimmune, inflammatory as well as cancerous disease models and are dependent on diet-derived substrates. The versatile mechanisms underlying both beneficial and detrimental effects of bacterial metabolites comprise diverse regulatory pathways in lymphocytes and non-immune cells including changes in the signaling, metabolic and epigenetic status of these. Consequently, SCFAs as strong modulators of immunometabolism and histone deacetylase (HDAC) inhibitors have been investigated as therapeutic agents attenuating inflammatory and autoimmune disorders. Moreover, BAs were shown to modulate the microbial composition itself by direct and indirect activation of both adaptive and innate immune genes. In this review, we will discuss the recent findings in the field of microbiota-derived metabolites, especially with respect to the molecular and cellular mechanisms of SCFA and BA biology in the context of intestinal and liver diseases.